2015
DOI: 10.1038/ncomms9997
|View full text |Cite|
|
Sign up to set email alerts
|

EPPS rescues hippocampus-dependent cognitive deficits in APP/PS1 mice by disaggregation of amyloid-β oligomers and plaques

Abstract: Alzheimer's disease (AD) is characterized by the transition of amyloid-β (Aβ) monomers into toxic oligomers and plaques. Given that Aβ abnormality typically precedes the development of clinical symptoms, an agent capable of disaggregating existing Aβ aggregates may be advantageous. Here we report that a small molecule, 4-(2-hydroxyethyl)-1-piperazinepropanesulphonic acid (EPPS), binds to Aβ aggregates and converts them into monomers. The oral administration of EPPS substantially reduces hippocampus-dependent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
84
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 63 publications
6
84
0
Order By: Relevance
“…The APP/PS1 model is known to show elevated levels of human Aβ by 6–7 months and impaired memory after 8 months of age. In the previous study, we observed clearance of Aβ aggregates and recovery of cognitive impairments in the same mouse model by long-term administration of EPPS in 10, 30 and 100 mg/kg/day7. To determine the minimum duration and dosage of EPPS administration for its therapeutic effect, the lower dosages of EPPS (0, 0.1, 1, and 10 mg/kg/day, n = 5, 7, 9, and 9, respectively) were administered orally to APP/PS1 mice daily for 10 weeks.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The APP/PS1 model is known to show elevated levels of human Aβ by 6–7 months and impaired memory after 8 months of age. In the previous study, we observed clearance of Aβ aggregates and recovery of cognitive impairments in the same mouse model by long-term administration of EPPS in 10, 30 and 100 mg/kg/day7. To determine the minimum duration and dosage of EPPS administration for its therapeutic effect, the lower dosages of EPPS (0, 0.1, 1, and 10 mg/kg/day, n = 5, 7, 9, and 9, respectively) were administered orally to APP/PS1 mice daily for 10 weeks.…”
Section: Resultsmentioning
confidence: 71%
“…Herein, we administered 4-(2-hydroxyethyl)-1-piperazinepropanesulphonic acid (EPPS), for its disease-modifying effect, and donepezil, for its symptomatic relief, together to aged APPswe/PS1-dE9 (amyloid precursor protein/presenilin protein 1) mice (APP/PS1). This mouse model produces elevated levels of human Aβ by expressing mutant human APP and PS1, which leads to development of Aβ plaques and AD-like cognitive impairments from 6 months of age78. EPPS was previously reported to directly disaggregate Aβ oligomers and plaques back into inert monomers in the brains of APP/PS1 mice7.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is an elementary way in which the living tissue retaliates to injury, infection or irritation by engendering the cardinal signs i.e., calor, dolor, function laesa, rubor and tumor [1]. Basically inflammation is categorized into two formsacute (rapid stimuli to injury by furnishing plasma proteins and leukocytes to the active site of injury) and chronic inflammation (perpetuated period of inflammation) [5,6]. Generally, acute inflammation leads to appendicitis, bronchitis, dermatitis, meningitis, sinusitis, sore throat and tonsillitis, while chronic inflammation causes aging, Alzheimer's, asthma, atherosclerosis, cancer, Crohn's disease, hepatitis, peptic ulcer, periodontitis, psoriasis, rheumatoid arthritis, sclerosis, sepsis and tuberculosis diseases [4].…”
Section: Discussionmentioning
confidence: 99%
“…[1] Inflammation process though a self-limiting process, it can become chronic and can further lead to several other serious inflammatory diseases. [2,3] The chronic inflammations may lead to various diseases such as cancer [4], atherosclerosis [5], Alzheimer's [6] and rheumatoid arthritis. [7] Historically, Willow bark extracts were used to treat the fever, inflammation and pain, thereafter the non-steroidal anti-inflammatory drugs (NSAIDs) which include organic acids and non-acidic compounds and coxibs (celecoxib, rofecoxib, etc) were drugs of choice to treat inflammation.…”
Section: Introductionmentioning
confidence: 99%